Using light, X-rays and electrons for evaluation of the nanostructure of layered materials - Djamil, John; Hansen, Anna-Lena; Backes, Claudia; Bensch, Wolfgang; Schürmann, Ulrich; Kienle, Lorenz; Düvel, Andre; Heitjans, Paul (Nanoscale, 2018)
As a case study for the evaluation of the nanostructure of layered materials, we report on results of the comprehensive characterization of high-energy ball-milled layered molybdenum disulfide (2H-MoS2) on different length scales. Analysis of X-ray powder diffraction patterns (XRPDs) including the Debye background at low scattering angles caused by uncorrelated single or few-layer MoS2 slabs (full scattering model), yield much more precise data about the average stacking degree than routine XRPD evaluation, and an estimation of the amount of single layer material is possible. Reflections with super Lorentzian line shape can be satisfactorily modeled assuming different stacking sequences induced by the mechanical forces exerted during the high-energy ball-mill process. An advanced analysis of UV-Vis spectra to determine layer number and lateral crystallite size, which was recently developed for liquid exfoliation materials, is used for the first time, and the results demonstrate the universal applicability of the approach. The data obtained with this analysis support the main findings of evaluation of the XRPD data. Both methods clearly evidence that increasing the duration of high-energy ball-mill treatment leads to an increase of material with decreasing average stacking and a reduction of the lateral size of the slabs. Finally, high-resolution transmission electron microscopy enabled identification of defects which can hardly be detected in XRPDs or in UV-Vis spectra.
Gesehen am 26.03.2020